2010
DOI: 10.12973/ejmste/75225
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technologies (ICT) in Biology Teaching in Slovenian Secondary Schools

Abstract: About two-thirds of Slovene secondary schools received computers equipped with dataloggers and sensors to be used in teaching Physics, Chemistry and Biology. Later it was recognized that only a couple of Biology teachers were using the donated equipment in their classrooms or laboratories. The questionnaire, intended to investigate the situation, was posted to schools which had received a donation. Based on the answers, it was possible to assign computer applications from one of the three groups. In the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
5
12
1
Order By: Relevance
“…The findings revealed positive correlation between ICT use and competences (r = .68, p < .01).This result is consistent with Sorgo, Verckovnik and Kocijancic (2010) who found high correlation between frequency of use of ICT, perceived value and teachers' competence in use of ICT among science teachers. They concluded that teachers' competence and confidence were predictors of using ICT in teaching.…”
Section: Discussionsupporting
confidence: 88%
“…The findings revealed positive correlation between ICT use and competences (r = .68, p < .01).This result is consistent with Sorgo, Verckovnik and Kocijancic (2010) who found high correlation between frequency of use of ICT, perceived value and teachers' competence in use of ICT among science teachers. They concluded that teachers' competence and confidence were predictors of using ICT in teaching.…”
Section: Discussionsupporting
confidence: 88%
“…Akkoyunlu and Orhan (2003) found in their study that while there is no difference in the self-efficacy beliefs regarding beginner level computer skills between male and female individuals, there is a difference favoring males in skills when it comes to the more complex use of computers. Many research studies are of the same view; the successful use of technology is connected to the attitude teachers develop towards computers (Albion, 2001;Kozma & Anderson, 2002;Hennessy, Ruthven & Brindley, 2005;Yushau, 2006;Šorgo, Verčkovnik & Kocijančič, 2010).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…Their importance was recognized by the Ministry of Education and Sport of Slovenia, and all general secondary schools received donations of such equipment between 2001 and 2004. In subsequent years it was recognized that such equipment was only rarely being used in the classroom ( Šorgo et al , 2010 ), so we can draw a similar conclusion to that of McFarlane and Sakellariou (2002) for England and Wales “that data loggers remain token rather than having found a place in routine science classes.” Even when they were used in the laboratory, their most important role was to facilitate the transition from cookbook labs to computer-supported cookbook labs.…”
Section: It Cannot Be Part Of the Curriculum Because It Can Be Of Usementioning
confidence: 53%